AVERROES, HAKEKAT DAN PENGARUHNYA TERHADAP RENAISSANCE - M. Bisri Djalil (LP2M Universitas Ibrahimy, 2014)
Ibnu Rusyd or popular in the West as Averroes is Moslem Philosopher are emerged di the West when Islamic thought in the East are declining appropriate in XII Century. Early, Averroes is the best translater of Aristotle and forward expansion formed his scholarly thought itself are Averroeism that amazing especially in the West. His thought be fondamen development of philosophical thought in the West and his contribution is very important for renaissance movement. Averroes is expert in the many discipline and very productive scholar, many books that he written expecially in philosophy translated in many language in the world and used as prime reference in many university in land of Europe. This way Averroes more famous in the West than in the East.